Overload of nursing work through Nursing Activities Score as an evaluating tool (Research, Society and Development, 2020)
The present study sought to identify the use of Nursing Activities Score (NAS) to evaluate the nursing work overload in national nursing studies. It is an integrative review of the literature, composed of: topic choice, bibliographic survey, formulation of guiding question, search of articles, reading and final writing of the work. The search for articles was carried out by consulting the VHL (Virtual Health Library) databases between 2009 and 2019, using data sources such as LILACS, BDENF, Medline and Scielo. Sixteen articles were selected, which raised several factors to be considered when dealing with workload for nursing, such as knowledge, technique, skills, leadership profile, staff dimensioning, care sites, and others that directly implicate the quality of care. Many studies confirm the NAS as a managerial tool, but still see the low utilization of it. It is necessary to promote the use of the instrument in addition to the ICU services in the country, with a view to improving the work, especially of nursing professionals, and providing a better management of care for patients.